Keunikan Tradisi Peusijuek: Simbol Harmoni dalam Masyarakat Aceh - Rahmah, Sri; Yulifar, Leli (JIM: Jurnal Ilmiah Mahasiswa Pendidikan Sejarah, 2025)
This article explores Peusijuek, a traditional Acehnese ritual deeply rooted in the regions cultural and Islamic values. As a symbol of blessing, peace, and harmony, Peusijuek is practiced during various life milestones, including weddings, pilgrimages, new beginnings, and personal achievements. Using a qualitative descriptive method with an ethnographic approach and supported by historical research, this study examines the symbolic meanings and cultural significance of Peusijuek, as well as the challenges it faces in the modern era. The findings show that Peusijuek reflects a harmonious integration of Islamic teachings and local traditions, making it an essential part of Acehnese identity. However, globalization and individualism have weakened the traditions transmission to younger generations. The study highlights the vital roles of traditional leaders, the Majelis Adat Aceh (MAA), educational institutions, and digital media in preserving and revitalizing this cultural heritage. Ultimately, Peusijuek serves not only as a ceremonial practice but also as a medium for cultural continuity, spiritual reflection, and social unity in Acehnese society.